Lithium ion battery positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material, lithium ion battery and electric equipment
By using alternately arranged loose layer and dense layer structures and optimized particle size distribution in the positive electrode material of lithium-ion battery, the problem that the positive electrode material in the prior art is difficult to take into account high specific capacity and cycle performance, and high-efficiency lithium is achieved Ion battery performance improvement and low cost preparation.
Patent Information
- Application Number
- CN202411375922.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
The precursors of the existing lithium-ion battery positive electrode material are difficult to take into account high specific capacity and good circulation performance.
The lithium-ion battery positive electrode material precursor adopts alternately arranged loose layer and dense layer structure. The total number of layers of loose layer and dense layer is ≥4 layers, and the particle size distribution is Span ≥0.8. It is prepared in a protective atmosphere by co-precipitation reaction. Control pH and ammonia concentration, optimize particle size distribution and structure.
It achieves a high Li+ migration rate and structural stability, improves the specific capacity and circulation performance of the positive electrode material, improves the volume energy density of lithium-ion batteries, and reduces the preparation cost.
Smart Images

Figure CN119284990A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and in particular to a lithium-ion battery positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery and electrical equipment. Background Art
[0002] Lithium-ion batteries are currently widely used as automotive power batteries due to their high specific capacity and rapid charge and discharge characteristics. The structural characteristics of lithium-ion battery cathode materials are mainly inherited from cathode material precursors, such as grain size, secondary particle size distribution, pore structure, grain arrangement, etc. Therefore, optimizing the structure of cathode material precursors is crucial to improving the performance of cathode materials. Existing cathode material precursors are difficult to achieve both high specific capacity and good cycle performance. Summary of the invention
[0003] The purpose of the present application is to provide a lithium-ion battery positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery and electrical equipment, aiming to solve the problem that the existing positive electrode material precursors are difficult to achieve both high specific capacity and good cycle performance at a low cost.
[0004] To achieve the above objectives, the present application provides a lithium-ion battery positive electrode material precursor, which includes alternating loose layers and dense layers, the total number of loose layers and dense layers is ≥4 layers, and the particle size distribution of the lithium-ion battery positive electrode material precursor Span = (D90-D10) / D50≥0.8.
[0005] In some embodiments, at least one of the following conditions is met:
[0006] A. The cross-sectional porosity of the lithium-ion battery cathode material precursor is 8%-15%;
[0007] B. The porosity of the loose layer is 9%-18%;
[0008] C. The porosity of the dense layer is 2%-8%;
[0009] D. In the lithium-ion battery positive electrode material precursor, the ratio of the average thickness of the dense layer to the average thickness of the loose layer is 0.8-3.5, optionally 1-2, and optionally 1.2-2.0.
[0010] In some embodiments, the thickness of the loose layer and the dense layer are independently 0.4 μm-1.3 μm;
[0011] Optionally, the thickness of the loose layer is 0.4-1.0 μm;
[0012] Optionally, the thickness of the dense layer is 0.7-1.3 μm.
[0013] In some embodiments, at least one of the following conditions is met:
[0014] A. The total number of loose layers and dense layers is 5-9;
[0015] B. The particle size distribution span of the lithium-ion battery cathode material precursor is 0.9-1.8;
[0016] In some embodiments, at least one of the following conditions is met:
[0017] A. The D50 of the cathode material precursor of lithium-ion batteries is 7-14 μm;
[0018] Optionally, the D50 of the lithium-ion battery cathode material precursor is 8-12 μm;
[0019] B. The specific surface area of the positive electrode material precursor of lithium-ion batteries is 11-22m 2 / g;
[0020] C. The compaction density of the positive electrode material precursor of lithium-ion batteries is 3.1-4.0g / cm 3 ;
[0021] D. The positive electrode material precursor of the lithium ion battery is a hydroxide containing nickel, which can be a hydroxide containing nickel, cobalt and manganese; optionally, the chemical formula of the positive electrode material precursor of the lithium ion battery is: (Ni x Co y Mn z M t )(OH)2, wherein 0.5≤x<1, 0≤y≤0.3, 0≤z≤0.3, x+y+z+t=1; M is selected from W, Al, Zr, Si, Mg, Mo, B, Sr or Ta, 0≤t≤0.05.
[0022] The present application also provides a method for preparing the above-mentioned lithium-ion battery positive electrode material precursor, comprising:
[0023] preparing a base solution comprising a precipitant and a complexing agent;
[0024] A metal salt solution, a precipitant solution and a complexing agent solution are introduced into the base liquid, and a coprecipitation reaction is carried out under a protective atmosphere, within a certain pH range and ammonia concentration, and a slurry is obtained by continuous overflow;
[0025] The slurry is subjected to solid-liquid separation to obtain a precursor of a positive electrode material for a lithium-ion battery.
[0026] In some embodiments, the preparation method satisfies at least one of the following conditions:
[0027] (1) The pH of the base solution is 10.5-11.5;
[0028] (2) The mass concentration of the complexing agent in the base solution is 4.0-8.0 g / L;
[0029] (3) The base liquid temperature rises to 70-80°C;
[0030] (4) The precipitant includes one or more of sodium carbonate, sodium hydroxide, and potassium hydroxide;
[0031] (5) The mass fraction of the precipitant solution is 10.0wt%-30.0wt%;
[0032] (6) The complexing agent includes one or more of ammonia water, ammonium carbonate, oxalic acid, citric acid, sodium citrate, ammonium citrate, and ammonium oxalate;
[0033] (7) The mass fraction of the complexing agent solution is 0.1wt%-30wt%;
[0034] (8) The metal salt solution is a solution containing at least a nickel salt; optionally, the metal salt solution further comprises a cobalt salt and / or a manganese salt;
[0035] (9) The sum of the mass concentrations of metal ions in the metal salt solution is 80-150 g / L;
[0036] (10) The pH of the coprecipitation reaction was 10.50-11.50 and fluctuated within the range of ±0.1;
[0037] (11) The free ammonia concentration of the coprecipitation reaction is 4.0-8.0 g / L;
[0038] (12) The stirring speed of the coprecipitation reaction is 450-550 r / min;
[0039] (13) The flow rate of the metal salt solution is 18% / h-22% / h of the volume of the reaction vessel;
[0040] (14) The flow rate of the precipitant is 7.0% / h-9.0% / h of the volume of the reaction vessel;
[0041] (15) The flow rate of the complexing agent is 0.02-4% / h of the volume of the reaction vessel;
[0042] (16) The solid content during the coprecipitation reaction is 80-120 g / L;
[0043] (17) A solution containing a doping element M may also be introduced into the base liquid, wherein the doping element M is at least one of W, Al, Zr, Si, Mg, Mo, B, Sr and Ta.
[0044] The present application also provides a lithium-ion battery positive electrode material, which is prepared from the above-mentioned lithium-ion battery positive electrode material precursor.
[0045] The present application also provides a lithium-ion battery, comprising the above-mentioned lithium-ion battery positive electrode material.
[0046] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0047] Compared with the prior art, the beneficial effects of this application include:
[0048] The lithium-ion battery positive electrode material precursor provided in the present application includes loose layers and dense layers arranged alternately, and the total number of loose layers and dense layers is ≥4 layers, and the particle size distribution span of the precursor is ≥0.8. The structure of alternating and uniformly distributed loose layers and dense layers can well balance the active area, pore structure, Li + Migration resistance, stress release ability and particle strength make the cathode material obtained by sintering the precursor to take into account the high Li + The migration rate and structural stability improve the specific capacity and cycle performance of the positive electrode material. The secondary particles of the precursor are widely distributed, and still have a wide particle size distribution after sintering into the positive electrode material. After compaction and winding into the positive electrode material, it has a higher density, which makes the lithium-ion battery have a higher volume energy density. At the same time, the wider particle size distribution can make this type of positive electrode material more convenient and low-cost to prepare, such as through a continuous method.
[0049] The positive electrode material, lithium-ion battery and electrical equipment provided in the present application have high specific capacity and cycle performance as well as high volume energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0051] Figure 1 It is a cross-sectional view of a secondary particle in the lithium-ion battery positive electrode material precursor of Example 1;
[0052] Figure 2 It is a cross-sectional view of a secondary particle in the lithium-ion battery positive electrode material precursor of Example 4;
[0053] Figure 3 It is a cross-sectional view of a secondary particle in the lithium-ion battery positive electrode material precursor of Example 6;
[0054] Figure 4It is a cross-sectional view of a secondary particle in the positive electrode material precursor of a lithium-ion battery in Comparative Example 2;
[0055] Figure 5 This is a cross-sectional view of a secondary particle in the lithium-ion battery positive electrode material precursor of Comparative Example 3. DETAILED DESCRIPTION
[0056] In these examples, parts and percentages are by mass unless otherwise indicated.
[0057] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0058] The present application provides a positive electrode material precursor for a lithium ion battery. The positive electrode material precursor for a lithium ion battery comprises loose layers and dense layers arranged alternately, the loose layers and the dense layers are coated layer by layer, the total number of the loose layers and the dense layers is ≥4 layers, for example, it can be 4 layers, 5 layers, 6 layers, 7 layers, 8 layers, 9 layers, 10 layers, 11 layers, 12 layers or more layers, and the particle size distribution Span of the positive electrode material precursor for a lithium ion battery is Span=(D90-D10) / D50≥0.8, for example It can be 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any value ≥0.8.
[0059] The lithium-ion battery positive electrode material precursor provided in the present application includes loose layers and dense layers arranged alternately, and the total number of loose layers and dense layers is ≥4 layers, and the particle size distribution span of the precursor is ≥0.8. The structure of alternating and uniformly distributed loose layers and dense layers can well balance the active area, pore structure, Li + Migration resistance, stress release ability and particle strength make the cathode material obtained by sintering the precursor to take into account the high Li + The migration rate and structural stability improve the specific capacity and cycle performance of the positive electrode material. The secondary particles of the precursor are widely distributed, and after sintering into the positive electrode material, they still have a wide particle size distribution. After compaction and winding into the positive electrode material, they have a higher density, which makes the lithium-ion battery have a higher volume energy density.
[0060] In a preferred embodiment, the total number of loose layers and dense layers is 5-9 layers.
[0061] In a preferred embodiment, the particle size distribution Span of the lithium-ion battery positive electrode material precursor is 0.9-1.8.
[0062] In some embodiments, the cross-sectional porosity of the lithium-ion battery positive electrode material precursor is 8%-15%, for example, it can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any value between 8% and 15%.
[0063] Among them, the porosity of the loose layer is 9%-18%, for example, it can be 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or any value between 9% and 18%; the porosity of the dense layer is 2%-8%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or any value between 2% and 8%.
[0064] In some embodiments, the thickness of the loose layer and the dense layer are independently 0.4 μm-1.3 μm, for example, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm or any value between 0.4 μm and 1.3 μm.
[0065] Optionally, the thickness of the loose layer is 0.4-1.0μm, for example, it can be 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm or any value between 0.6μm and 1.0μm; optionally, the thickness of the dense layer is 0.7-1.3μm, for example, it can be 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm or any value between 0.7μm and 1.3μm.
[0066] In the embodiment of the present application, the thickness of the loose layer and the dense layer are both average thicknesses. Optionally, the ratio of the average thickness of the loose layer to the average thickness of the loose layer is 0.8-3.5, such as 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.4, 2.8, 3.0, 3.5.
[0067] In some embodiments, the D50 of the positive electrode material precursor of a lithium ion battery is 7-14 μm, for example, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or any value between 7 and 14 μm. Optionally, the D50 of the positive electrode material precursor of a lithium ion battery is 8-12 μm.
[0068] In some embodiments, the specific surface area of the lithium-ion battery positive electrode material precursor is 11-22 m 2 / g, for example, 11m 2 / g, 12m2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g or 11-22m 2 Any value between / g.
[0069] In some embodiments, the compaction density of the lithium-ion battery positive electrode material precursor is 3.1-4.0 g / cm 3 , for example, it can be 3.1 g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 、3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4.0g / cm 3 or 3.1-4.0g / cm 3 Any value in between.
[0070] In some embodiments, the positive electrode material precursor of the lithium ion battery is a hydroxide containing nickel, which may be a hydroxide containing nickel, cobalt and manganese; optionally, the chemical formula of the positive electrode material precursor of the lithium ion battery is: (Ni x Co y Mn z M t )(OH)2, wherein 0.5≤x<1, 0≤y≤0.3, 0≤z≤0.3, x+y+z+t=1; M is selected from W, Al, Zr, Si, Mg, Mo, B, Sr or Ta, 0≤t≤0.05.
[0071] The present application also provides a method for preparing the above-mentioned lithium-ion battery positive electrode material precursor, comprising:
[0072] preparing a base solution comprising a precipitant and a complexing agent;
[0073] A metal salt solution, a precipitant solution and a complexing agent solution are introduced into the bottom liquid, and a coprecipitation reaction is carried out under a protective atmosphere, within a certain pH range and ammonia concentration, and a slurry is obtained by continuous overflow;
[0074] The slurry is subjected to solid-liquid separation to obtain a precursor of a positive electrode material for a lithium-ion battery.
[0075] In some embodiments, the pH of the base liquid is 10.5-11.5; the mass concentration of the complexing agent in the base liquid is 4.0-8.0 g / L; the base liquid is heated to 70-80°C; a solution containing a doping element M can also be passed into the base liquid, and the doping element M is at least one of W, Al, Zr, Si, Mg, Mo, B, Sr and Ta.
[0076] In some embodiments, the precipitant includes one or more of sodium carbonate, sodium hydroxide, and potassium hydroxide; the mass fraction of the precipitant solution is 10.0 wt%-30.0 wt%.
[0077] In some embodiments, the complexing agent includes one or more of ammonia water, ammonium carbonate, oxalic acid, citric acid, sodium citrate, ammonium citrate, and ammonium oxalate; the mass fraction of the complexing agent solution is 0.1wt%-30wt%.
[0078] In some embodiments, the metal salt solution is a solution containing at least nickel salt; optionally, the metal salt solution also includes cobalt salt and / or manganese salt; the sum of the mass concentrations of metal ions in the metal salt solution is 80-150 g / L.
[0079] In some embodiments, the pH of the coprecipitation reaction is 10.50-11.50, and fluctuates within the range of ±0.1; the free ammonia concentration of the coprecipitation reaction is 4.0-8.0 g / L; the stirring speed of the coprecipitation reaction is 450-550 r / min; the flow rate of the metal salt solution is 18% / h-22% / h of the volume of the reaction container; the flow rate of the precipitant is 7.0% / h-9.0% / h of the volume of the reaction container; the flow rate of the complexing agent is 0.02-4% / h of the volume of the reaction container; the solid content during the coprecipitation reaction is 80-120 g / L.
[0080] The present application also provides a lithium-ion battery positive electrode material, which is prepared from the above-mentioned lithium-ion battery positive electrode material precursor.
[0081] The present application also provides a lithium-ion battery, comprising the above-mentioned lithium-ion battery positive electrode material.
[0082] The present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.
[0083] The lithium-ion battery positive electrode material, lithium-ion battery and electrical equipment provided in the present application have high specific capacity and cycle performance as well as high volume energy density.
[0084] The implementation scheme of the present application will be described in detail below in conjunction with specific examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be regarded as limiting the scope of the present application.
[0085] Example 1
[0086] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.9002 Co 0.0491 Mn 0.0507 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 10.12 μm, Span=1.35, and a compacted density of 3.88 g / cm 3 , the porosity is 10.22%. In the precursor, the molar amount of Ni accounts for 90.02% of the total metal ion molar amount, the molar amount of Co accounts for 4.91% of the total metal ion molar amount, and the molar amount of Mn accounts for 5.07% of the total metal ion molar amount. The cross-sectional structure has 6.3 layers of dense alternating structure, the average thickness of the loose layer is 0.63μm, the average thickness of the dense layer is 1.05μm, and the density-loose layer thickness ratio (i.e., the average thickness of the dense layer: the average thickness of the loose layer) is 1.67. It should be noted that in this application, loose and dense are qualitative expressions based on the amount of porosity, and do not constitute a limitation on a specific porosity. For example, in two adjacent layers, the one with a higher porosity is defined as a loose layer, and the one with a lower porosity is defined as a dense layer.
[0087] In the present application, the determination of the layer is as follows: the layer is distinguished according to the density of the structure in the cross-sectional view, and the boundary of each layer is fitted from the inside to the outside in a circle or ellipse or in a manner parallel to the outer contour of the secondary particle; the determination of the average number of layers (referred to as the average number of layers) is as follows: at least 5 secondary particles with a diameter (maximum radial dimension) in the range of (0.9-1.1)×D50 are randomly selected in the cross-sectional view, and the average value is taken after counting all the number of layers (keeping one decimal place); the thickness of the layer is as follows: a cross-sectional view of a secondary particle with a diameter in the range of (0.9-1.1)×D50 is selected, and 5 pairs of points are randomly selected from two adjacent fitted boundaries in the cross-sectional view (the line connecting each pair of points is 1 / 4 of the diameter of the secondary particle). Perpendicular to the fitted boundary), measure the distance between 5 pairs of points and take the average value as the thickness of the layer, to be precise, the thickness of a loose layer (or dense layer) of the secondary particle; average thickness of the layer: after measuring the thickness of the layer, measure the thickness of all loose layers (or dense layers) in the cross section of the secondary particle in the same way, and calculate the average value to obtain the average thickness of the layer, to be precise, the average thickness of the loose layer (or dense layer) of the secondary particle; take 3 secondary particles, and calculate the average value based on the average thickness of the loose layer (or dense layer) of the above secondary particles, to obtain the average thickness of the loose layer (or dense layer) of the precursor material. Unless otherwise specified, the thickness of the loose layer (or dense layer) in this application refers to the average thickness of the loose layer (or dense layer) of the precursor material, and the number of layers refers to the average number of layers.
[0088] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0089] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=90.0:5.0:5.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0090] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 11.00 and a free ammonia concentration of 6.0 g / L.
[0091] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min. The pH of the reaction process is controlled to fluctuate within 11.00±0.10, the free ammonia concentration is 6.0g / L, and the solid content in the reactor is 110g / L.
[0092] (4) The D50 particles meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.9002 Co 0.0491 Mn 0.0507 (OH)2, its cross-sectional view is as follows Figure 1 shown.
[0093] This embodiment also provides a lithium ion battery positive electrode material, and the preparation method thereof is as follows:
[0094] The positive electrode material precursor obtained above was mixed with the lithium source compound in a molar ratio of 1:(1.02-1.05), ball-milled with polyurethane balls for 3 hours, and calcined at 750-800°C in an air atmosphere for 6 hours to obtain the ternary lithium-ion battery positive electrode material of Example 1.
[0095] This embodiment also provides a lithium-ion battery buckling performance testing method, which is as follows:
[0096] (1) Electrochemical performance test was carried out using a button-type semi-electrode: the above-mentioned positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1, and the slurry was evenly coated on an aluminum foil with a length and width of 1×2 cm to prepare a positive electrode sheet.
[0097] (2) The negative electrode sheet is made of metallic lithium sheet, and the electrolyte is 1 mol / L LiPF6 EC:DMC:EMC=1:1:1 (volume ratio). The battery case, positive and negative electrode sheets, diaphragm (PE double-layer ceramic diaphragm), spring sheet, and gasket are assembled into a button battery in a vacuum glove box.
[0098] (3) Electrochemical performance test was performed using the Blue Electric Test System CT3002A, 2.5-4.25V (1C = 200mAh g -1 ) conditions, the discharge capacity and cycle retention rate tests were carried out under the measuring temperature of 25℃±1℃ and the humidity of <40%.
[0099] The preparation methods of the positive electrode materials for lithium-ion batteries and the testing methods of the lithium-ion battery buckling performance in the following examples and comparative examples are the same.
[0100] Example 2
[0101] The main difference between Example 2 and Example 1 is that the preparation process is different (the solid content in the reactor is different).
[0102] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.9008 Co 0.0495 Mn 0.0497 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 10.06 μm, Span=1.62, and a compacted density of 3.94 g / cm 3 , porosity is 14.34%. In the precursor, the molar amount of Ni accounts for 90.08% of the total metal ion molar amount, the molar amount of Co accounts for 4.95% of the total metal ion molar amount, and the molar amount of Mn accounts for 4.97% of the total metal ion molar amount. The cross-sectional structure has 9.1 layers of alternating dense and sparse structures, with an average thickness of 0.58 μm for the loose layer, an average thickness of 0.96 μm for the dense layer, and a dense-loose layer thickness ratio of 1.66.
[0103] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0104] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=90.0:5.0:5.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0105] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 11.00 and a free ammonia concentration of 7.0 g / L.
[0106] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min, and the pH of the reaction process is controlled to fluctuate within 11.00±0.1, the free ammonia concentration is 7.0g / L, and the solid content in the reactor is 80g / L.
[0107] (4) The D50 particles meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.9008 Co 0.0495 Mn 0.0497 (OH)2.
[0108] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1.
[0109] Example 3
[0110] The main difference between Example 3 and Example 1 is that the molar ratio of Ni, Co and Mn ions is different.
[0111] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.8011 Co 0.0995 Mn 0.0994 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 12.03 μm, Span=0.86, and a compacted density of 3.19 g / cm 3 , porosity is 11.22%. In the precursor, the molar amount of Ni accounts for 80.11% of the total molar amount of metal ions, and the molar amount of Co accounts for 9.95% of the total molar amount of metal ions. The cross-sectional structure has 7.2 layers of alternating dense and sparse structures, with an average thickness of 0.71 μm for the loose layer, an average thickness of 1.12 μm for the dense layer, and a density-loose layer thickness ratio of 1.58.
[0112] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0113] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=80.0:10.0:10.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0114] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 11.00 and a free ammonia concentration of 6.0 g / L.
[0115] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min. The pH of the reaction process is controlled to fluctuate within 11.00±0.10, the free ammonia concentration is 6.0g / L, and the solid content in the reactor is 100g / L.
[0116] (4) The particles with D50 meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.8011 Co 0.0995 Mn 0.0994 (OH)2.
[0117] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1.
[0118] Example 4
[0119] The main difference between Example 4 and Example 1 is that the molar ratio of Ni, Co and Mn ions is different.
[0120] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.7021 Co 0.2495 Mn 0.0484 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 9.23 μm, Span=1.28, and a compacted density of 3.25 g / cm 3, porosity is 8.16%. In the precursor, the molar amount of Ni accounts for 70.21% of the total metal ion molar amount, the molar amount of Co accounts for 24.95% of the total metal ion molar amount, and the molar amount of Mn accounts for 4.84% of the total metal ion molar amount. The cross-sectional structure has 7.3 layers of alternating dense and sparse structures, with an average thickness of 0.76 μm for the loose layer, an average thickness of 1.02 μm for the dense layer, and a dense-loose layer thickness ratio of 1.34.
[0121] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0122] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=70.0:25.0:5.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0123] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 500 r / min, and the bottom liquid conditions were adjusted to a pH value of 10.90 and a free ammonia concentration of 7.0 g / L.
[0124] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min. The pH of the reaction process is controlled to fluctuate within 10.90±0.1, the free ammonia concentration is 7.0g / L, and the solid content in the reactor is 100g / L.
[0125] (4) The particles with D50 meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.7021 Co 0.2495 Mn 0.0484 (OH)2, its cross-sectional view is as follows Figure 2 shown.
[0126] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1.
[0127] Example 5
[0128] The main difference between Example 5 and Example 1 is that the molar ratio of Ni, Co and Mn ions is different.
[0129] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.6011 Co 0.1995 Mn 0.1994 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 9.73 μm, Span=1.12, and a compacted density of 3.31 g / cm 3 , porosity is 9.26%. In the precursor, the molar amount of Ni accounts for 60.11% of the total metal ion molar amount, the molar amount of Co accounts for 19.95% of the total metal ion molar amount, and the molar amount of Mn accounts for 19.94% of the total metal ion molar amount. The cross-sectional structure has 8.4 layers of alternating dense and sparse structures, with an average thickness of 0.57 μm for the loose layer, an average thickness of 0.98 μm for the dense layer, and a dense-loose layer thickness ratio of 1.72.
[0130] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0131] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=60.0:20.0:20.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 80 g / L.
[0132] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 550 r / min, and the bottom liquid conditions were adjusted to a pH value of 10.90 and a free ammonia concentration of 7.5 g / L.
[0133] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min. The pH of the reaction process is controlled to fluctuate within 10.90±0.1, the free ammonia concentration is 7.5g / L, and the solid content in the reactor is 100g / L.
[0134] (4) The particles with D50 meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.6011 Co 0.1995 Mn 0.1994 (OH)2.
[0135] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1
[0136] Example 6
[0137] The main difference between Example 6 and Example 1 is that W element is doped.
[0138] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.9002 Co 0.0483 Mn 0.0496 W 0.0019 (OH)2. In the precursor, Ni, Co, Mn, and W ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 10.31 μm, Span=1.32, and a compacted density of 3.64 g / cm 3 , porosity is 11.96%. In the precursor, the molar amount of Ni accounts for 90.02% of the total metal ion molar amount, the molar amount of Co accounts for 4.83% of the total metal ion molar amount, the molar amount of Mn accounts for 4.96% of the total metal ion molar amount, and the molar amount of W accounts for 0.19% of the total metal ion molar amount. The cross-sectional structure has a 5.4-layer dense alternating structure, the average thickness of the loose layer is 0.88μm, the average thickness of the dense layer is 1.21μm, and the dense-loose layer thickness ratio is 1.37.
[0139] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0140] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution, and prepare a metal salt solution according to the molar ratio of Ni:Co:Mn=90.0:5.0:5.0, in which the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L. Prepare a sodium tungstate salt solution with a W ion concentration of 0.5 g / L.
[0141] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 11.00 and a free ammonia concentration of 6.0 g / L.
[0142] (3) The materials were pumped into the reactor at a set flow rate, and metal salt solution (flow rate was 20% / h of the available volume of the reactor), sodium tungstate salt solution (flow rate was 10% / h of the available volume of the reactor), sodium hydroxide solution (flow rate was 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate was 0.60% / h of the available volume of the reactor) were introduced to carry out a coprecipitation reaction. The reaction slurry reached the upper limit of the reactor volume and began to overflow. The stirring speed during the reaction process was maintained at 450 r / min, and the pH of the reaction process was controlled to fluctuate within 11.00±0.1. The free ammonia concentration was 6.0 g / L and the solid content in the reactor was 110 g / L.
[0143] (4) The D50 particles meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.9002 Co 0.0483 Mn 0.0496 W 0.0019 (OH)2, its cross-sectional view is as follows Figure 3 shown.
[0144] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1.
[0145] Example 7
[0146] The main difference between Example 7 and Example 1 is that Mg element is doped.
[0147] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.9003 Co 0.0451 Mn 0.0495 Mg 0.0011 (OH)2. In the precursor, Ni, Co, Mn, and Mg ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 11.31 μm, Span=1.42, and a compacted density of 3.67 g / cm 3, porosity is 12.33%. In the precursor, the molar amount of Ni accounts for 90.03% of the total metal ion molar amount, the molar amount of Co accounts for 4.51% of the total metal ion molar amount, the molar amount of Mn accounts for 4.95% of the total metal ion molar amount, and the molar amount of Mg accounts for 0.11% of the total metal ion molar amount. The cross-sectional structure has 7.3 layers of alternating dense and sparse structures, with an average thickness of 0.56 μm for the loose layer, an average thickness of 1.08 μm for the dense layer, and a dense-loose layer thickness ratio of 1.93.
[0148] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0149] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution, and prepare a metal salt solution according to the molar ratio of Ni:Co:Mn=90.0:5.0:5.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L. Prepare a magnesium sulfate solution with a magnesium ion concentration of 0.5 g / L.
[0150] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 11.00 and a free ammonia concentration of 6.0 g / L.
[0151] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), magnesium sulfate solution (flow rate is 5% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 500r / min, and the pH of the reaction process is controlled to fluctuate within 11.00±0.1, the free ammonia concentration is 6.0g / L, and the solid content in the reactor is 110g / L.
[0152] (4) Continue the reaction until particles with D50 meeting the requirements are obtained, filter and wash the overflow positive electrode material precursor slurry, and dry, sieve and demagnetize the filter cake to obtain Ni 0.9003 Co 0.0451 Mn 0.0495 Mg 0.0011 (OH)2.
[0153] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1.
[0154] Example 8
[0155] The main difference between Example 8 and Example 1 is that different pH values account for different proportions in the pH cycle control period.
[0156] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.9001 Co 0.0498 Mn 0.0501 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 10.31 μm, Span=1.38, and a compacted density of 3.71 g / cm 3 , porosity is 9.33%. In the precursor, the molar amount of Ni accounts for 90.01% of the total metal ion molar amount, the molar amount of Co accounts for 4.98% of the total metal ion molar amount, and the molar amount of Mn accounts for 5.01% of the total metal ion molar amount. The cross-sectional structure has 7.1 layers of alternating dense and sparse structures, with an average thickness of 0.41 μm for the loose layer, an average thickness of 1.28 μm for the dense layer, and a dense-loose layer thickness ratio of 3.12.
[0157] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0158] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=90.0:5.0:5.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0159] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 10.90 and a free ammonia concentration of 7.5 g / L.
[0160] (3) The materials were pumped into the reactor at a set flow rate, and metal salt solution (flow rate was 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate was 8.0% / h of the available volume of the reactor) and ammonia water (flow rate was 0.60% / h of the available volume of the reactor) were introduced to carry out a coprecipitation reaction. The reaction slurry reached the upper limit of the reactor volume and began to overflow. The stirring speed during the reaction process was maintained at 450 r / min, and the pH of the reaction process was controlled to fluctuate within 11.00±0.1. The low pH period accounted for a larger proportion than that in Example 1. The free ammonia concentration was 6.0 g / L and the solid content in the reactor was 110 g / L.
[0161] (4) The particles with D50 meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.9001 Co 0.0498 Mn 0.0501 (OH)2.
[0162] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1.
[0163] Example 9
[0164] The main difference between Example 9 and Example 3 is that the particle size and solid content at the reaction end point are different.
[0165] This embodiment provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.8012 Co 0.0995 Mn 0.0993 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 15.21 μm, Span=1.31, and a compacted density of 3.31 g / cm 3 , porosity is 10.95%. In the precursor, the molar amount of Ni accounts for 80.12% of the total metal ion molar amount, the molar amount of Co accounts for 9.95% of the total metal ion molar amount, and the molar amount of Mn accounts for 9.93% of the total metal ion molar amount. The cross-sectional structure has 11.2 layers of alternating dense and sparse structures, with an average thickness of 0.55 μm for the loose layer, an average thickness of 0.92 μm for the dense layer, and a dense-loose layer thickness ratio of 1.67.
[0166] The positive electrode material precursor of the lithium-ion battery of this embodiment is prepared by the following steps:
[0167] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=80.0:10.0:10.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0168] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 10.80 and a free ammonia concentration of 8.0 g / L.
[0169] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min, and the pH of the reaction process is controlled to fluctuate within 10.80±0.10, the free ammonia concentration is 8.0g / L, and the solid content in the reactor is 160g / L.
[0170] (4) The D50 particles meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.8012 Co 0.0995 Mn 0.0993 (OH)2.
[0171] This embodiment also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode plate and a battery, and the preparation method is the same as that of embodiment 1.
[0172] Comparative Example 1
[0173] The main difference between this comparative example and Example 1 is: the different preparation processes.
[0174] This comparative example provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.9012 Co 0.0486 Mn 0.0502 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 10.92 μm, Span=1.41, and a compacted density of 3.29 g / cm 3, porosity is 12.54%. In the material, the molar amount of Ni accounts for 90.12% of the total metal ion molar amount, the molar amount of Co accounts for 4.86% of the total metal ion molar amount, and the molar amount of Mn accounts for 5.02% of the total metal ion molar amount. The cross-sectional structure has a 3.6-layer dense alternating structure, the average thickness of the loose layer is 0.41μm, the average thickness of the dense layer is 1.28μm, and the dense-loose layer thickness ratio is 3.12.
[0175] The lithium-ion battery positive electrode material precursor of this comparative example is prepared by the following steps:
[0176] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=90.0:5.0:5.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0177] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 10.40 and a free ammonia concentration of 6.0 g / L.
[0178] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min. The pH of the reaction process is controlled to fluctuate within 10.40±0.1, the free ammonia concentration is 6.0g / L, and the solid content in the reactor is 110g / L.
[0179] (4) The D50 particles meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.9012 Co 0.0486 Mn 0.0502 (OH)2.
[0180] This comparative example also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode sheet and a battery, and the preparation method is the same as that of Example 1.
[0181] Comparative Example 2
[0182] The main difference between this comparative example and Example 3 is: the different preparation processes.
[0183] This comparative example provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.8011 Co 0.0995 Mn 0.0994 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 12.03 μm, Span=1.33, and a compacted density of 3.57 g / cm 3 , porosity is 8.03%. In the precursor, the molar amount of Ni accounts for 80.11% of the total metal ion molar amount, the molar amount of Co accounts for 9.95% of the total metal ion molar amount, and the molar amount of Mn accounts for 9.94% of the total metal ion molar amount. The cross-sectional structure has a 3.2-layer dense alternating structure, the average thickness of the loose layer is 1.48μm, the average thickness of the dense layer is 2.86μm, and the dense-loose layer thickness ratio is 1.93.
[0184] The lithium-ion battery positive electrode material precursor of this comparative example is prepared by the following steps:
[0185] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=80.0:10.0:10.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0186] (2) Add pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), ammonia solution (mass percentage concentration of 10.5%), and 5 kg of seeds with a particle size D50 of 2.8 μm into the reactor. The seed preparation conditions are: pH 11.20, ammonia concentration 4.0 g / L, and metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0% / h of the available volume of the reactor) and ammonia solution (flow rate is 0.60% / h of the available volume of the reactor) are introduced to carry out coprecipitation reaction. After D50 reaches the target requirement, it is dried for use. Nitrogen is introduced as protective gas, the reaction temperature is 75°C, the reaction speed is 450 r / min, and the bottom liquid conditions are adjusted to fluctuate within 11.00±0.1 and the free ammonia concentration is 6.0 g / L.
[0187] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min. The pH of the reaction process is controlled to fluctuate within 11.00±0.1, the free ammonia concentration is 6.0g / L, and the solid content in the reactor is 100g / L.
[0188] (4) The D50 particles meeting the requirements are obtained by reaction, and the overflowed positive electrode material precursor slurry is filtered and washed. The filter cake is dried, sieved, and demagnetized to obtain Ni 0.8011 Co 0.0995 Mn 0.0994 (OH)2, its cross-sectional view is as follows Figure 4 shown.
[0189] This comparative example also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode sheet and a battery, and the preparation method is the same as that of Example 1.
[0190] Comparative Example 3
[0191] The main difference between this comparative example and Example 3 is: the different preparation processes.
[0192] This comparative example provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.7981 Co 0.1005 Mn 0.1014 (OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 9.83 μm, Span=0.32, and a compacted density of 2.49 g / cm 3 , porosity is 10.29%. In the precursor, the molar amount of Ni accounts for 79.81% of the total metal ion molar amount, the molar amount of Co accounts for 10.05% of the total metal ion molar amount, and the molar amount of Mn accounts for 10.14% of the total metal ion molar amount. The cross-sectional structure has 7.1 layers of alternating dense and sparse structures, with an average thickness of 0.66 μm for the loose layer, an average thickness of 0.97 μm for the dense layer, and a dense-loose layer thickness ratio of 1.47.
[0193] The lithium-ion battery positive electrode material precursor of this comparative example is prepared by the following steps:
[0194] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=80.0:10.0:10.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0195] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 11.00 and a free ammonia concentration of 6.0 g / L.
[0196] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to concentrate. The stirring speed of the reaction process is gradually reduced from 450r / min to 300r / min, the pH value of the reaction process is gradually reduced from 11.00 to 10.00, the free ammonia concentration is maintained at 6.0g / L, and the solid content in the reactor gradually accumulates from 0 to 200g / L.
[0197] (4) Continue the reaction until particles with D50 meeting the requirements are obtained, filter and wash the overflow positive electrode material precursor slurry, and dry, sieve and demagnetize the filter cake to obtain Ni 0.7981 Co 0.1005 Mn 0.1014 (OH)2, its cross-sectional view is as follows Figure 5 shown.
[0198] This comparative example also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode sheet and a battery, and the preparation method is the same as that of Example 1.
[0199] Comparative Example 4
[0200] The main difference between this comparative example and Example 4 is: the different preparation processes.
[0201] This comparative example provides a nickel, cobalt, manganese ternary lithium ion battery positive electrode material precursor, the chemical formula is Ni 0.8012 Co 0.1005 Mn 0.0983(OH)2. In the precursor, Ni, Co, and Mn ions are evenly distributed in the bulk phase of the material; the secondary particles of the precursor are spherical, with a particle size D50 of 11.28 μm, Span = 0.56, and a compacted density of 2.66 g / cm 3 , porosity is 8.46%. In the precursor, the molar amount of Ni accounts for 80.12% of the total metal ion molar amount, the molar amount of Co accounts for 10.05% of the total metal ion molar amount, and the molar amount of Mn accounts for 9.83% of the total metal ion molar amount. The cross-sectional structure has 6.8 layers of alternating dense and sparse structures, with an average thickness of 0.63 μm in the loose layer and an average thickness of 1.05 μm in the dense layer.
[0202] The lithium-ion battery positive electrode material precursor of this comparative example is prepared by the following steps:
[0203] (1) Prepare appropriate amounts of nickel sulfate solution with a metal ion concentration of 120 g / L, cobalt sulfate solution with a metal ion concentration of 120 g / L, and manganese sulfate solution with a metal ion concentration of 120 g / L. Mix the nickel sulfate solution, cobalt sulfate solution, and manganese sulfate solution to prepare a metal salt solution according to a molar ratio of Ni:Co:Mn=80.0:10.0:10.0, wherein the sum of the mass concentrations of nickel, cobalt, and manganese ions is 120 g / L.
[0204] (2) Pure water, sodium hydroxide solution (mass percentage concentration of 20.5%), and ammonia solution (mass percentage concentration of 10.5%) were added into the reactor, and nitrogen was introduced as a protective gas. The reaction temperature was 75° C., the reaction speed was 450 r / min, and the bottom liquid conditions were adjusted to a pH value of 11.00 and a free ammonia concentration of 10.0 g / L.
[0205] (3) Feed the materials into the reactor by pumping at a set flow rate, and introduce metal salt solution (flow rate is 20% / h of the available volume of the reactor), sodium hydroxide solution (flow rate is 8.0±1.0% / h of the available volume of the reactor) and ammonia water (flow rate is 0.60% / h of the available volume of the reactor) to carry out a coprecipitation reaction. The reaction slurry reaches the upper limit of the reactor volume and begins to overflow. The stirring speed of the reaction process is maintained at 450r / min. The pH of the reaction process is controlled to fluctuate within 11.00±0.1, the free ammonia concentration is 10.0g / L, and the solid content in the reactor is 100g / L.
[0206] (4) Continue the reaction until particles with D50 meeting the requirements are obtained, filter and wash the overflow positive electrode material precursor slurry, and dry, sieve and demagnetize the filter cake to obtain Ni 0.8012 Co 0.1005 Mn 0.0983 (OH)2.
[0207] This comparative example also provides a lithium ion battery positive electrode material, a lithium ion battery positive electrode sheet and a battery, and the preparation method is the same as that of Example 1.
[0208] The growth mechanism of the positive electrode material precursor of the present application: the crystallization rate and crystal surface energy are regulated by parameters such as pH, ammonia concentration, and flow rate, forming an alternating, balanced state of "fine particles (high porosity, high surface energy) → dense stacking structure (a spontaneous trend to reduce surface energy, and the crystal growth rate increases after dense stacking) → fine particles", and a sparse and dense alternating structure is formed under a certain residence time.
[0209] The physical and chemical indicators and performance indicators of the lithium-ion battery positive electrode material precursors of various embodiments and comparative examples are shown in Table 1, and the performance indicators of the lithium-ion batteries of various embodiments and comparative examples are shown in Table 2.
[0210] Table 1 Physical and chemical indicators and performance indicators of embodiments and comparative examples
[0211]
[0212] Among them, Span and D50 were tested using Malvern 3000 laser particle size analyzer, with reference to the standard GB / T 19077-2016 Particle Size Analysis Laser Diffraction Method. The porosity of this application was calculated using Image J software.
[0213] Compaction test conditions: The test was conducted using the Sansi UIM 7305 compaction density meter. The test method was as follows: 1g of the material to be tested was placed in a clean mold with a hole radius of 6.5mm. The mold was then placed on the pressure plate of the equipment and the test pressure was selected to be 3T for testing.
[0214] Table 2 Performance indicators of lithium-ion batteries of embodiments and comparative examples
[0215]
[0216]
[0217] The lithium ion battery positive electrode material precursor prepared in Comparative Example 1 has the same other indicators as the lithium ion battery positive electrode material precursor in Example 1 except that it does not have the special ring layer structure of the present application, but the particle strength, discharge gram capacity, discharge volume capacity, and cycle retention rate are all lower than those in Example 1. Specifically, compared with Example 1, the average number of layers of the loose layer-dense layer alternating arrangement structure in Comparative Example 1 is 3.6 layers, which is significantly lower than 6.3 layers in Example 1.
[0218] The lithium ion battery positive electrode material precursor prepared in Comparative Example 2 has no special ring layer structure of the present application, and the other indicators are basically the same as those of the lithium ion battery positive electrode material precursor in Example 3, and the corresponding discharge gram capacity, discharge volume capacity, and cycle retention rate are all lower than those in Example 3. Specifically, compared with Example 3, the average number of layers of the loose layer-dense layer alternating arrangement structure in Comparative Example 2 is 3.2 layers, which is significantly lower than 7.2 layers in Example 3.
[0219] The lithium-ion battery positive electrode material precursor prepared in Comparative Example 3 is basically the same as Example 3 in terms of indicators except that the Span is lower, and the discharge gram capacity, discharge volume capacity, and cycle retention rate are all lower than those of Example 3. Specifically, compared with Example 3, the Span of Comparative Example 3 is 0.32, which is significantly lower than 0.8 of Example 3. Comparative Example 3 does not have the characteristics of the higher Span of the present application. In the subsequent processing of positive electrode materials and battery cells, the compaction density of the active material is low, and the content of active material is less under the same battery cell volume. Therefore, the capacity of Comparative Example 3, especially the volume capacity, is significantly lower than that of Example 3.
[0220] The lithium ion battery positive electrode material precursor prepared in Comparative Example 4 is basically the same as that in Example 4 except for Span, and is lower than that in Example 4 in terms of particle strength, discharge gram capacity, discharge volume capacity, and cycle retention rate. Specifically, compared with Example 4, the Span of Comparative Example 4 is 0.56, which is significantly lower than 1.28 of Example 4. Comparative Example 4 does not have the characteristic of higher Span of the present invention, so Comparative Example 4 is significantly lower than Example 4 in capacity, especially volume capacity.
[0221] Examples 1 to 5 all prepared precursor structures with a certain number of loose layers and dense layers arranged alternately. Although they have different ratios of Ni, Co, and Mn elements, they all have higher secondary particle spans, higher particle strength, discharge capacity, and better cycle performance overall. The specific reasons are as follows: the appropriate span makes the positive electrode material have a higher packing density, which is conducive to the use of volumetric capacity; the number of loose layers and dense layers arranged alternately is greater than 4 layers, which reduces the number of grain boundaries and reduces Li compared to materials with fewer layers. + On the other hand, the transmission resistance is beneficial to the release of stress caused by the change of grain volume during charging and discharging, and is also beneficial to the utilization of capacity and maintenance of structure.
[0222] Examples 6 to 7 prepared two metal element (W / Mg)-doped cathode material precursors having the structure and physicochemical index characteristics of the present application, which demonstrated excellent performance in both discharge capacity and cycle retention rate, indicating that the cathode material precursors of lithium-ion batteries doped with metal elements can also improve performance when having the structure and physicochemical index characteristics of the present application.
[0223] The precursor of Example 8 has a lower average loose layer thickness and a thicker average dense layer thickness than the precursor of Example 1, and is lower than Example 1 in both discharge capacity and cycle retention rate.
[0224] The number of coils of the precursor of Example 9 is greater than that of Example 3. Although the discharge capacity and cycle retention rate are lower than those of Example 3, they are both higher than those of the comparative example.
[0225] It can be seen from Examples 1 to 9 that the lithium-ion battery positive electrode material precursor prepared based on the present application having a dense and sparse alternating structure of more than 4 layers and a higher span has both good volumetric capacity and cycle performance.
[0226] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A lithium-ion battery positive electrode material precursor, characterized in that: The lithium-ion battery positive electrode material precursor comprises loose layers and dense layers arranged alternately, the total number of the loose layers and the dense layers is ≥4 layers, and the particle size distribution Span of the lithium-ion battery positive electrode material precursor is Span=(D90-D10) / D50≥0.
8.
2. The lithium-ion battery positive electrode material precursor according to claim 1, characterized in that: At least one of the following conditions is met: A. The cross-sectional porosity of the lithium-ion battery cathode material precursor is 8%-15%; B. The porosity of the loose layer is 9%-18%; C. The porosity of the dense layer is 2%-8%; D. In the lithium-ion battery positive electrode material precursor, the ratio of the average thickness of the dense layer to the average thickness of the loose layer is 0.8-3.5; optionally, the ratio of the average thickness of the dense layer to the average thickness of the loose layer is 1.2-2.
3. The lithium-ion battery positive electrode material precursor according to claim 1, characterized in that: The thickness of the loose layer and the dense layer are independently 0.4 μm-1.3 μm; Optionally, the thickness of the loose layer is 0.4-1.0 μm; Optionally, the thickness of the dense layer is 0.7-1.3 μm.
4. The lithium-ion battery positive electrode material precursor according to claim 1, characterized in that: At least one of the following conditions is met: A. The total number of the loose layer and the dense layer is 5-9 layers; B. The particle size distribution Span of the lithium-ion battery positive electrode material precursor is 0.9-1.
8.
5. The lithium-ion battery positive electrode material precursor according to any one of claims 1 to 4, characterized in that: At least one of the following conditions is met: A. The D50 of the lithium ion battery cathode material precursor is 7-14 μm; Optionally, the D50 of the lithium-ion battery positive electrode material precursor is 8-12 μm; B. The specific surface area of the lithium ion battery positive electrode material precursor is 11-22m 2 / g; C. The compaction density of the lithium ion battery positive electrode material precursor is 3.1-4.0 g / cm 3 ; D. The positive electrode material precursor of the lithium ion battery is a hydroxide containing nickel, which can be a hydroxide containing nickel, cobalt and manganese; optionally, the chemical formula of the positive electrode material precursor of the lithium ion battery is: (Ni x Co y Mn z M t )(OH)2, wherein 0.5≤x<1, 0≤y≤0.3, 0≤z≤0.3, x+y+z+t=1; M is selected from W, Al, Zr, Si, Mg, Mo, B, Sr or Ta, 0≤t≤0.
05.
6. A method for preparing a lithium-ion battery positive electrode material precursor according to any one of claims 1 to 5, characterized in that: include: preparing a base solution comprising a precipitant and a complexing agent; A metal salt solution, a precipitant solution and a complexing agent solution are introduced into the base liquid, and a coprecipitation reaction is carried out under a protective atmosphere, within a certain pH range and ammonia concentration, and the slurry is obtained by continuous overflow; The slurry is subjected to solid-liquid separation to obtain the lithium-ion battery positive electrode material precursor.
7. The method for preparing a positive electrode material precursor for a lithium-ion battery according to claim 6, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The pH of the base solution is 10.5-11.5; (2) The mass concentration of the complexing agent in the base solution is 4.0-8.0 g / L; (3) the base liquid is heated to 70-80° C.; (4) The precipitant includes one or more of sodium carbonate, sodium hydroxide, and potassium hydroxide; (5) The mass fraction of the precipitant solution is 10.0wt%-30.0wt%; (6) The complexing agent includes one or more of ammonia water, ammonium carbonate, oxalic acid, citric acid, sodium citrate, ammonium citrate, and ammonium oxalate; (7) The mass fraction of the complexing agent solution is 0.1wt%-30wt%; (8) The metal salt solution is a solution containing at least a nickel salt; optionally, the metal salt solution further comprises a cobalt salt and / or a manganese salt; (9) The sum of the mass concentrations of metal ions in the metal salt solution is 80-150 g / L; (10) The pH of the coprecipitation reaction is 10.50-11.50 and fluctuates within the range of ±0.1; (11) The free ammonia concentration of the coprecipitation reaction is 4.0-8.0 g / L; (12) The stirring speed of the coprecipitation reaction is 450-550 r / min; (13) The flow rate of the metal salt solution is 18% / h-22% / h of the volume of the reaction vessel; (14) The flow rate of the precipitant is 7.0% / h-9.0% / h of the volume of the reaction vessel; (15) The flow rate of the complexing agent is 0.02-4% / h of the volume of the reaction vessel; (16) The solid content during the coprecipitation reaction is 80-120 g / L; (17) A solution containing a doping element M may also be introduced into the base liquid, wherein the doping element M is at least one of W, Al, Zr, Si, Mg, Mo, B, Sr and Ta.
8. A positive electrode material for a lithium ion battery, characterized in that: Prepared from the lithium-ion battery positive electrode material precursor according to any one of claims 1 to 5.
9. A lithium ion battery, characterized in that: The lithium-ion battery positive electrode material comprises the positive electrode material of claim 8.
10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.